2019
DOI: 10.5946/ce.2018.160
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Efficacy of Endoscopic Ultrasound Elastography in Differentiating Solid Pancreatic Lesions: A Single-Center Experience

Abstract: Background/Aims Endoscopic ultrasound (EUS) has a limited ability to determine the nature of solid pancreatic lesions (SPLs). Most recent ultrasound processors are provided with elastography software, which allows quantification of the tissue hardness. The aim of this study is to evaluate the effectiveness of the elasticity score (ES) and strain ratio (SR) in the differentiation of benign pancreatic lesions from malignant pancreatic lesions. Methods The study had a retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
5
0
2
Order By: Relevance
“…Pixel values within the region of interest were converted to color images within the range of 0 (red) for minimum hardness to 255 (blue) for maximum hardness, which created a distribution histogram. Reported evaluation methods by strain elastography include a qualitative evaluation method using color pattern [ 35 , 36 , 37 , 38 , 39 ] and a quantitative evaluation method measuring strain ratio, strain histogram, and neural network [ 22 , 25 , 40 , 41 , 42 , 43 , 44 , 45 ]. On the other hand, shear wave elastography can measure the absolute value of tissue hardness by calculating the propagation velocity of shear waves and Young’s modulus.…”
Section: Eusmentioning
confidence: 99%
“…Pixel values within the region of interest were converted to color images within the range of 0 (red) for minimum hardness to 255 (blue) for maximum hardness, which created a distribution histogram. Reported evaluation methods by strain elastography include a qualitative evaluation method using color pattern [ 35 , 36 , 37 , 38 , 39 ] and a quantitative evaluation method measuring strain ratio, strain histogram, and neural network [ 22 , 25 , 40 , 41 , 42 , 43 , 44 , 45 ]. On the other hand, shear wave elastography can measure the absolute value of tissue hardness by calculating the propagation velocity of shear waves and Young’s modulus.…”
Section: Eusmentioning
confidence: 99%
“…ej., visualización del gráfico de deformación) (70,(79)(80)(81) . Por su parte, el VPP de 89,8 % (IC 95 %: 79,5 %-95,3 %), VPN de 94,3 % (IC 95 %: 84,6 %-98,1 %) y exactitud del 92,0 % (IC 95 %: 85,4 %-95,7 %) son resultados congruentes con los encontrados en un estudio recientemente publicado retrospectivo de 116 pacientes (97 con lesiones malignas y 19 con lesiones benignas), con una mediana de edad de 55,9 años; se usó un punto de corte de SR de 7,75 con una especificidad del 99,9 %, sensibilidad del 90,7 %, VPP del 99,9 %, VPN del 67,9 % y precisión del 92,2 % (82) .…”
Section: Indeterminadaunclassified
“…Malignant tissue is often more rigid than the normal surrounding tissue; thus, EUS elastography can differentiate between malignant and nonmalignant lesions. As a result, this technique has been applied in the diagnostic workup of PMs and their associated LNs[ 2 - 4 ]. EUS elastography is considered an accurate imaging technique for characterizing and detecting pancreatic lesions[ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…EUS elastography can be used to evaluate PMs and their associated LNs through qualitative and quantitative analyses; the former involves the analysis of color maps, while the latter is achieved by assessing the strain ratio (SR). However, previous studies, such as the one published by Altonbary et al [ 4 ], have reported differences in the SR cutoff value and the optimal internal sensitivity and specificity, suggesting a potential limitation of this technique[ 3 , 4 ]. The accuracy of this technique in differentiating malignant from nonmalignant lesions has only been assessed for masses consisting of solid tissue.…”
Section: Introductionmentioning
confidence: 99%